2016
DOI: 10.1037/ipp0000045
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparisons of Teachers’ Knowledge and Misconceptions of ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is among the most prevalent disorders of childhood and adolescence worldwide. Teachers are likely to play an important role in multiple stages of the help-seeking process (e.g., problem recognition) for children with ADHD. This study examined the relationship of prior exposure and ADHD training with teachers’ knowledge and misconceptions of the disorder in a multinational sample. Teachers ( N = 2,307) from 9 countries (Czech Republic, Germany, Greece, Iraq, the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 58 publications
1
32
0
5
Order By: Relevance
“…This issue may increase the risk of delayed diagnosis, misdiagnosis or improper school treatment of children with ADHD [ 12 , 13 ]. A multinational study on teachers from nine countries indicated that professional ADHD training predicted adequate knowledge in the majority of countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue may increase the risk of delayed diagnosis, misdiagnosis or improper school treatment of children with ADHD [ 12 , 13 ]. A multinational study on teachers from nine countries indicated that professional ADHD training predicted adequate knowledge in the majority of countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, teachers make recommendations, appropriate or inappropriate, about ADHD to the parents, who tend to follow such recommendations [16, 23]. In turn, parents frequently turn to teachers for information about ADHD [19].…”
Section: Introductionmentioning
confidence: 99%
“…La literatura ha venido señalando el papel de la experiencia como fuente de conocimiento sobre TDAH. Así, el nivel de conocimientos del profesorado es mayor cuando ha trabajado con alumnado afectado (Sciutto et al, 2000, Kos et al, 2004Jarque et al, 2007;Jones y Chronis-Tuscano, 2008), o bien conoce algún amigo o familiar diagnosticado con TDAH (Sciutto et al, 2016). Los resultados del presente estudio hacen extensivo ese papel a los futuros profesionales del ámbito escolar, aunque matizando que en nuestro caso la experiencia previa es muy reducida y el efecto de esta variable es bajo.…”
Section: Discussionunclassified
“…Ello refleja el papel relevante de estos profesionales y la necesidad de que posean la formación suficiente para participar en la detección e intervención con el alumnado aquejado de TDAH. En general, los estudios realizados sobre maestros constatan un moderado o bajo nivel de conocimientos (Anderson, Watt, Noble y Shanley, 2012;Sciutto et al, 2016;Soroa, Gorostiaga y Balluerka, 2016;Vereb y DiPerna, 2004), coincidiendo en señalar mayores carencias en lo que respecta a etiología del TDAH que al conocimiento de los síntomas básicos y su tratamiento. En la misma dirección se han venido orientando los resultados obtenidos al explorar los conocimientos de los futuros maestros, quienes presentan también carencias relevantes (Akram, Thomson, Boyter y McLarty, 2009;Bekle, 2004;Canu y Mancil, 2012;Jarque y Tárraga, 2009;Liang y Gao, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation